Establishment of health related physical fitness evaluation system for school adolescents aged 12–16 in Pakistan: a cross-sectional study - Hamdani, Syed Muhammad Zeeshan Haider; Zhuang, Jie; Hadier, Syed Ghufran; Khurram, Haris; Hamdani, Syed Danish Haider; Danish, Shaista Shireen; Fatima, Syeda Urooj; Tian, Wang (Frontiers in Public Health, 2023)
Background: The decline in adolescent physical fitness is a significant global public health concern, and Pakistan is no exception. The country's absence of a health-related physical fitness (HRPF) evaluation system has compounded this issue. To bridge this gap, this study aims to develop a scientifically-based HRPF evaluation system for the adolescent population that meets international standards. The evaluation system identifies at-risk children and improves adolescent health outcomes, including obesity, cardiovascular and musculoskeletal disorders, chronic diseases, and psychological illnesses, through crucial physical fitness evaluation. This study specifically aims to establish an HRPF evaluation system for school adolescents aged 12-16 in Pakistan. Methods: A cross-sectional study was conducted among 2970 school adolescents aged 12-16 years in the South Punjab, Pakistan. The study used a stratified sampling technique to select participants. The HRPF evaluation system included four components: cardiorespiratory endurance, core muscular endurance, muscular strength and body composition. Data were collected through standardized tests and anthropometric measurements. Results: The study's results indicated that the HRPF evaluation scoring system was feasible and valid for evaluating the HRPF of school adolescents in the South Punjab region of Pakistan. The results of the evaluation system categorized participants into five groups based on their performance: excellent (6.2%), good (24.9%), medium (50.7%), poor (17%), and very poor (1.2%). Conclusion: The study establishes an HRPF evaluation system for Pakistani school adolescents. This system lays the foundation for implementing effective strategies to improve their physical health. The findings offer valuable insights to policymakers, health professionals, and educators, enabling them to promote fitness and devise impactful interventions for enhancing HRPF in this population.